Analisis Butir Soal Ujian Sekolah Berstandar Nasional dengan Pendekatan Klasik dan Teori Respon Butir Mata Pelajaran Matematika - Baso Intang Sappaile; Triyanto Pristiwaluyo (Seminar Nasional LP2M UNM, 2019)
This study aims to determine: 1) the validity of the contents of the test and the internal validity of the test items, 2) the reliability of the test, 3) the characteristics of the test items according to Classical Theory, and 4) the characteristics of the test items according to the USBN Grain Response Theory in Junior High School Mathematics. The study population was all USBN test items in mathematics in state junior high schools in East Luwu Regency, South Sulawesi in the academic year 2017/2018. Test takers from Wasuponda 1 Middle School represent Schools with accreditation A consisting of 302 students, Towuti 1 Public Schools represent Schools with accreditation B consisting of 253 students, and Wasuponda 2 Public Schools represent unaccredited schools consisting of 29 students. The total response of students of the National Middle School Mathematics Standard School Examination which will be analyzed as many as 584 answer sheets. Data obtained through documentation about the score points of the SMP USBN test results. Data were analyzed with classical theory and item response theory. National Mathematics Standardized School Middle School Examination Test in Luwu Timur District 2017/2018 School Year concluded that: 1) had fulfilled the criteria of content validity and internal validity, 2) did not meet the element of test reliability because the reliability coefficient was 0.561, 3) using the classical theory of entry in the difficult category, the power difference in the category is not good and most of the deceivers have been functioning effectively, 4) by using the analysis of the 3PL model the power of the different categories of good test items, 5) the different power of each test item can be observed on the characteristic curve of each test item , 6) the level of difficulty most of the test items are in the difficult category and pseudo guesses are in the good category.